Descarte correto do lixo eletrônico: a importância da conscientização para a sustentabilidade - Oliveira, Anneheide de [UNESP] (2015)
Electronic waste is currently the fastest growing solid waste on our planet. It is a hazardous waste when disposed of in landfills. On the other hand, it is valuable because it contains precious metals in their composition. Thus, their disposal has become a challenge to society. Despite the complexity of the recycling process, the components can be reused as a raw material in industrial processes and reinserted, avoiding the extraction of natural resources and providing environmental benefits. The university extension project "AdministrAÇÔES”, developed by students of Public Administration FCL/Car and coordinated by Prof. Dr. Patricia BorbaMarchetto, on its axis relative to eletronic waste, titled “Look Conscious E-waste " it is the awareness of the proper disposal of e-waste through lectures aiming to provide information to the population of Araraquara especially children and young people are the key elements for the evolution sustainable society.